Penyelesaian Sengketa Ketidaklengkapan Persyaratan Pemilihan Kepala Desa Jaten, Kabupaten Blitar - Mustofa Kamil (Hakim, 2023)
The purpose of this research is to understanding the mechanism of dispute resolution resulting from The Election of the Head of Jaten Village in Blitar Regency, with a focus on the conformity of legal cosiderations in the PTUN Surabaya Decision Number 235/B/2014/PT.TUN.SBY with the applicable laws and regulations. The author uses normative research method with library research approach to gather legal materials, including sources from experts, research findings, and journals related to the mechanism of dispute resolution based on the laws and regulations.